Evaluating project management criteria using fuzzy analytic hierarchy process - Mohammed, Husam Jasim; Al-Jubori, Ihsan Ali Mubarak; Mat Kasim, Maznah (AIP Publishing LLC, 2019)
Project management is one of the most important issues to fulfil organizational objectives. The project management criteria are playing a vital role for completion of any project. The aim of this paper is to evaluate five main project criteria (time, cost, quality, risk, and safety) mathematically by using a multi-criteria method in order to assist stakeholders or project managers in decision-making. The fuzzy Analytic Hierarchy Process (AHP) is selected with the use of triangular fuzzy numbers for pairwise comparison scales in prioritizing the criteria in managing projects. Utilizing the fuzzy AHP technique can facilitate uncertainty in doing evaluation. In this study, one expert who is a project manager with many years of experience was asked to carry out the evaluation. The results show that the expert’s main concern in managing project is time, and cost is the second important. The study demonstrates how uncertainty in making evaluation of multiple criteria can be solved by using fuzzy method such as fuzzy AHP, in contrary to the crisp or the traditional AHP which is based on specific values, the evaluator(s) are always ambiguous and vague to give exact judgment. Hence, the application of this fuzzy method can make the assessment outcomes more accurate, scientific, and objective. It is anticipated that this work may serve as a support tool for stakeholders in improving the project management quality level.